2002
DOI: 10.1107/s1600536802009674
|View full text |Cite
|
Sign up to set email alerts
|

Monoclinic form of ethyl 4-aminobenzoate (benzocaine)

Abstract: The structure of the title compound, C9H11NO2, (I), comprises a flat mol­ecule arranged, head‐to‐tail, in linear ribbon arrays via a N—H⋯O=C association. These ribbons end‐on form a herring‐bone structure interconnected via N—H⋯N association. The structure was first determined in 1987 [Sinha & Pattabhi (1987). Proc. Indian Acad. Sci. Chem. Sci. 98, 229–234] in the orthorhombic space group P212121, with R = 0.120, whereas similar cell dimensions and an increased β angle in the present study resulted in monoclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 1 publication
2
14
0
Order By: Relevance
“…This and the fact that crystals suitable for diffuse scattering studies can readily be grown make it an ideal compound for this type of study. Room-temperature single-crystal X-ray diffraction studies reveal the existence of two polymorphs for BZC, one crystallizing as monoclinic P2 1 =c [polymorph (I); Lynch & McClenaghan, 2002], the other as orthorhombic P2 1 2 1 2 1 [polymorph (II); Sinha & Pattabhi, 1987]. As a result of the present studies a third low-temperature polymorph [polymorph (III)] has been found.…”
Section: Introductionsupporting
confidence: 61%
“…This and the fact that crystals suitable for diffuse scattering studies can readily be grown make it an ideal compound for this type of study. Room-temperature single-crystal X-ray diffraction studies reveal the existence of two polymorphs for BZC, one crystallizing as monoclinic P2 1 =c [polymorph (I); Lynch & McClenaghan, 2002], the other as orthorhombic P2 1 2 1 2 1 [polymorph (II); Sinha & Pattabhi, 1987]. As a result of the present studies a third low-temperature polymorph [polymorph (III)] has been found.…”
Section: Introductionsupporting
confidence: 61%
“…Until now three polymorphs of BZC were known. At ambient conditions, BZC exists in two forms: monoclinic polymorph (I) (space group P2 1 /c, Lynch & McClenaghan, 2002) and orthorhombic polymorph (II) (space group P2 1 2 1 2 1 ; Sinha & Pattabhi, 1987). On cooling to 150 K, polymorph (II) undergoes a solid-to-solid phase transition to polymorph (III) of monoclinic symmetry, space group P112 1 (Chan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…I, and SLC hydrate suitable for SCXRD could be produced, and the crystal structures were determined. The crystal structures of local anesthetics, which were known before this study [BZC (36,37), procaine (PC) (38), PCHC (39,40), dyclonine hydrochloride (DCNHC) (41), LDCHC hydrate (42), BPCHC (43), BPCHC ethanolate, R-BPCHC (44), and mepivacaine hydrochloride (MPCHC) (45)], gave no indication on conformational polymorphism (Table IV) because they all show just one conformation of the molecule [except the monomorphic LAA compounds lidocaine (LDC) (46) and cinchocaine hydrochloride hydrate (CCCHC) (47,48), which consist of two conformers in the asymmetric unit]. The polymorphic crystal structures of this study confirm that the crystal polymorphism of these compounds is caused by the conformational flexibility of the molecules (see Structural Aspects).…”
Section: Single Crystal X-ray Diffractometrymentioning
confidence: 99%